2010
DOI: 10.1186/1471-2164-11-471
|View full text |Cite
|
Sign up to set email alerts
|

Positional differences in the wound transcriptome of skin and oral mucosa

Abstract: BackgroundWhen compared to skin, oral mucosal wounds heal rapidly and with reduced scar formation. Recent studies suggest that intrinsic differences in inflammation, growth factor production, levels of stem cells, and cellular proliferation capacity may underlie the exceptional healing that occurs in oral mucosa. The current study was designed to compare the transcriptomes of oral mucosal and skin wounds in order to identify critical differences in the healing response at these two sites using an unbiased appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
201
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(222 citation statements)
references
References 39 publications
19
201
0
2
Order By: Relevance
“…Furthermore, gene expression analyses reveal that MMP-1, MMP-9, and MMP-10 are transcriptionally induced in Pyk2-overexpressing keratinocytes and, therefore, may function as candidate effectors of Pyk2 to promote wound healing. Consistent with this assumption, wound transcriptome profiling revealed that the MMP group of genes that included MMP-1, MMP-9, and MMP-10 genes was a significantly enriched category among early upregulated genes in murine skin wounds, along with two additional MMPs, MMP-8t and MMP-13 (4). MMP gene expression is primarily regulated at the transcriptional level (reviewed in Ref.…”
Section: C906mentioning
confidence: 54%
“…Furthermore, gene expression analyses reveal that MMP-1, MMP-9, and MMP-10 are transcriptionally induced in Pyk2-overexpressing keratinocytes and, therefore, may function as candidate effectors of Pyk2 to promote wound healing. Consistent with this assumption, wound transcriptome profiling revealed that the MMP group of genes that included MMP-1, MMP-9, and MMP-10 genes was a significantly enriched category among early upregulated genes in murine skin wounds, along with two additional MMPs, MMP-8t and MMP-13 (4). MMP gene expression is primarily regulated at the transcriptional level (reviewed in Ref.…”
Section: C906mentioning
confidence: 54%
“…In a recent study, the overall gene expression of mucosal and skin wounds was compared via microarray analysis. 5 Among the multiple differences that were noted, the data suggested that wound healing in these two tissues might exhibit differential signatures of apoptosis related genes, such as tumor necrosis factor alpha (TNF-a) and several downstream signaling factors. 5 Apoptosis can be induced via two main pathways, termed intrinsic and extrinsic.…”
Section: Introductionmentioning
confidence: 99%
“…4 Altogether, the phases of wound healing after mucosal injury are shortened in duration and generally have reduced gene and protein expression changes in comparison to skin wound healing. 5 Apoptosis is an important mechanism for cellular elimination during wound healing and maintains tissue homeostasis in normal, uninjured tissue. In a recent study, the overall gene expression of mucosal and skin wounds was compared via microarray analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, several categories of genes were overexpressed in cultured skin substitutes compared with native skin, including genes associated with hyperproliferative skin or activated keratinocytes. 18 In another study, Chen et al 19 investigated why oral mucosal wounds heal more rapidly and with reduced scar formation than cutaneous wounds. They obtained biopsies of both oral mucosal and skin wounds and used microarrays to compare transcriptomes to determine the critical differences in the healing response at these two sites.…”
Section: Human Wound-healing Microarray Studiesmentioning
confidence: 99%
“…Their results demonstrated dramatically different reactions to injury between skin and mucosal wounds. 19 In a study by Greco et al, 20 the gene expression profiles of thermally injured human skin were observed with microarrays. For the analysis, skin samples were…”
Section: Human Wound-healing Microarray Studiesmentioning
confidence: 99%